Caracterização populacional de Cichla kelberi (Perciformes: Cichlidae) no reservatório do Lobo (Broa), Brotas / Itirapina - SP - Souza, Jussara Elias de (2007)
The Cichla kelberi population was characterized in terms of sexual proportion, size structure and some reproductive aspects. The collects were made in two distinct periods. The first, from November 2002 to November 2003 and the second, from December 2004 to May 2006. The sexual proportion showed significantly difference from 1:1 with predominance of females. Total length varied from 3.4 to 40.1cm, with large frequency on the small sized classes. These smallest individuals occurred around all the year, but mainly in the warmer months. Females and males reached similar maximum length. Individuals with Mature or Partial Spent gonads occurred mainly from November to April, indicating that Cichla kelberi has a long reproductive period, a biological evidence that it is a species well adapted in this reservoir, showing partial spawning and an absolute fecundity ranging from 6089 to 6908 oocytes.